2022
DOI: 10.1108/joepp-03-2021-0080
|View full text |Cite
|
Sign up to set email alerts
|

Empowering leadership and healthcare workers performance outcomes in times of crisis: the mediating role of safety climate

Abstract: PurposeDrawing upon the norm of reciprocity and social exchange theory, the purpose of this study is to propose and empirically test a model on the relationship between empowering leadership and employees' work-related outcomes during the COVID-19 pandemic. In this model, safety climate was theorized as an intervening mechanism between (1) empowering leadership and organizational citizenship behavior (OCB) and (2) empowering leadership and risk-taking behavior.Design/methodology/approachUsing a cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 107 publications
2
14
0
Order By: Relevance
“…It was also noted in the literature that positive attributes of leaders can lead to notable positive attitudes toward the job and the organization ( Amundsen and Martinsen, 2015 ). In the same context, studies have also reported that empowering leadership is a determinant of creativity due to delegation and autonomy that is provided to employees ( Short and Rinehart, 1992 ; Wu and Short, 1996 ; Atik and Celik, 2020 ; Dahleez and Aboramadan, 2022 ). This study argues that by increasing autonomy for university teachers, they are more likely to be engaged and involved with their jobs, and use new approaches or techniques to better perform their tasks.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It was also noted in the literature that positive attributes of leaders can lead to notable positive attitudes toward the job and the organization ( Amundsen and Martinsen, 2015 ). In the same context, studies have also reported that empowering leadership is a determinant of creativity due to delegation and autonomy that is provided to employees ( Short and Rinehart, 1992 ; Wu and Short, 1996 ; Atik and Celik, 2020 ; Dahleez and Aboramadan, 2022 ). This study argues that by increasing autonomy for university teachers, they are more likely to be engaged and involved with their jobs, and use new approaches or techniques to better perform their tasks.…”
Section: Discussionmentioning
confidence: 98%
“…In this research, it is conceptualized that autonomy and competence can be promoted for teachers that can enhance their work processes and mental resources that they need ( Atik and Celik, 2020 ; Helland et al, 2020 ). In contrast, when resources are scarce and demands are high (i.e., education sector and teaching profession), negative outcomes can arise such as decreased job satisfaction, lack of motivation and engagement, burnout, and work-life conflict (e.g., Aboramadan, 2020 ; Dahleez and Aboramadan, 2022 ; Khawand and Zargar, 2022 ). The role of appropriate leadership (e.g., empowering, responsible, and ethical) is highly influential in improving work environment for employees considering the limitations that the organization face (i.e., during and after the pandemic), and available resources (e.g., economic, risk management and policy and change management).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, it can be argued that employees working under the umbrella of an effective HPWS tend to develop positive perceptions of the safety climate at their organization. As such organizations are perceived to be supportive and committed to safety (Dahleez et al, 2022;Aboramadan and Dahleez, 2022;Huang et al, 2016), employees are expected to show outstanding levels of trust and confidence (Kath et al, 2010), and thus feel safe, which would ultimately lead them to exhibit positive behaviors such as risk-taking behavior and OCB. Based on the above, the following two hypotheses are posited: H3.…”
Section: Er 446mentioning
confidence: 99%
“…According to the findings, 79.3 million US workers are affected by some form of workplace bullying, with leaders being the most frequent perpetrators (in 65% of bullying instances; WBI, 2021). Research on the topic of leadership has long discussed and examined the influence leaders have on their followers (Dahleez et al. , 2022; Fuller et al.…”
Section: Introductionmentioning
confidence: 99%